2006
DOI: 10.1016/j.brainresbull.2006.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic investigation of methylenetetrahydrofolate reductase (MTHFR) and catechol-O-methyl transferase (COMT) in multiple sclerosis

Abstract: Multiple sclerosis (MS) is a chronic neurological disease characterized by central nervous system (CNS) inflammation and demyelination. The C677T substitution variant in the methylenetetrahydrofolate reductase (MTHFR) gene has been associated with increased levels of circulating homocysteine and is a mild risk factor for vascular disease. Higher blood levels of homocysteine have also been reported in MS. Thus, the C677T mutation of the MTHFR gene may influence MS susceptibility.Noradrenaline, a neurotransmitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…Accordingly, Tajouri et al (2006) C677T genotype of an Australian MS and unaffected populations and showed that mutant MTHFR genotype (T/T) was slightly, however not significantly, more presented in the MS group. Interestingly, in their study, the T/T was 1.5-fold more prevalent in MS patients compared to control group, which is very close to what we have observed in our study (1.7-fold increase).…”
Section: Discussionmentioning
confidence: 91%
“…Accordingly, Tajouri et al (2006) C677T genotype of an Australian MS and unaffected populations and showed that mutant MTHFR genotype (T/T) was slightly, however not significantly, more presented in the MS group. Interestingly, in their study, the T/T was 1.5-fold more prevalent in MS patients compared to control group, which is very close to what we have observed in our study (1.7-fold increase).…”
Section: Discussionmentioning
confidence: 91%
“…On the contrary, horizontal agarose gels are easier to prepare and stain, non toxic and also allow large number of samples to be loaded on a single gel through the use of multiple adjacent combs. By eliminating the constant recognition sequence found in close proximity to the recognition sequence of interest, which is a novel approach, the ability of medium percentage agarose gels to resolve the informative bands within a short electrophoresis time was significantly increased, as the difference in length between the indicative fragments was increased from 18 bp, which is commonly found in the literature [21][22][23][24][25], to 36 bp, which is unprecedented. Therefore, the use of high concentration agarose gels (4-5%) which are costly and difficult to handle and prepare, can be avoided [28,29].…”
Section: Resultsmentioning
confidence: 73%
“…By eliminating the constant recognition sequence found in close proximity to the recognition sequence of interest, which is a novel approach, the ability of medium percentage agarose gels to resolve the informative bands within a short electrophoresis time was significantly increased, as the difference in length between the indicative fragments was increased from 18 bp, which is commonly found in the literature [21][22][23][24][25], to 36 bp, which is unprecedented. Therefore, the use of high concentration agarose gels (4-5%) which are costly and difficult to handle and prepare, can be avoided [28,29]. Furthermore, it was possible to reduce electrophoresis buffer concentration used down to 20% of that commonly used in order to allow the application of a high electric field strength (16 V/cm ) resulting in extremely short separation time (16 min) and distance (3cm) .…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations